Changes in laws on emissions reduction, implying a change in the production process, chemical composition and distribution of automotive fuels - Kamiński, Arkadiusz (Studia Ecologiae et Bioethicae, 2014)
This article presents an analysis of legal actions taken to determine fuel quality requirements, emission standards adapted to meet global and European health and environmental protection programs, including the World Wide Fuel Charter and other relevant directives. The series of subsequent consecutive legal regulations, including more and more restrictive automotive fuel requirements, aimed at decreasing the negative impact of vehicle usage on the natural environment and human health. The results of the assessment of the implementation of the mentioned regulations in Poland are presented as well.